2012
DOI: 10.4040/jkan.2012.42.7.1095
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Blue-collar Workers' Risk Perception of Cardiovascular Disease

Abstract: Purpose: The purpose of this study was to investigate the contribution of actual cardiovascular disease (CVD) risk, as well as, individual, psychosocial, and work-related factors as predictors of CVD risk perception among Korean blue-collar workers. Methods: The participants were 238 Korean blue-collar workers who worked in small companies. Data were collected through a survey; anthropometric and blood pressure measures; and blood sampling for lipid levels. Results: Blue-collar workers had high actual CVD risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 26 publications
0
13
1
1
Order By: Relevance
“…Therefore, McLeroy emphasized, there must be an integrated consideration of personal factors and organizational factors. Moreover, recognizing disease risk factors can act as a major factor, which affects the health promotional behavior of individuals [ 8 ]. Therefore, it is important for healthcare staff who engage both workers and employers to identify the risk factors for cardiovascular disease in the practical context and apply them when planning health promotional programs to prevent and manage cardiovascular diseases in workers from small–medium-sized companies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, McLeroy emphasized, there must be an integrated consideration of personal factors and organizational factors. Moreover, recognizing disease risk factors can act as a major factor, which affects the health promotional behavior of individuals [ 8 ]. Therefore, it is important for healthcare staff who engage both workers and employers to identify the risk factors for cardiovascular disease in the practical context and apply them when planning health promotional programs to prevent and manage cardiovascular diseases in workers from small–medium-sized companies.…”
Section: Introductionmentioning
confidence: 99%
“…Major risk factors for CVD in addition to a sedentary lifestyle and a diet high in saturated fat and cholesterol include family history, age, sex, elevated low-density-lipoprotein cholesterol (LDL-C), decreased high-density-lipoprotein cholesterol (HDL-C), hypertension, cigarette smoking, and diabetes mellitus [24]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies have also clearly shown that blue-collar workers tend to have low CVD-risk perceptions ( Fahs et al, 2013 ; Al-Tamimi et al, 2017 ; Fox, 2019 ). Although recent studies have identified CVD risk perceptions among workers in general ( Hwang et al, 2012 ), this is not well described among blue-collar workers. It is therefore important to include CVD-risk perception as a cognitive perceptual factor in the HPM.…”
Section: Discussionmentioning
confidence: 99%